Building religious character in students: a qualitative study of youth information and counseling centers - Jum Anidar; Nursyamsi Nursyamsi; Afsah Diminurman; Engkizar Engkizar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study explores how the Youth Information and Counseling Center (PIK-R) at Madrasah Aliyah Negeri 2 Padang contributes to the formation of students’ religious character. While PIK-R is widely recognized as a forum for social and psychological guidance, its role in shaping religious values through students’ lived experiences remains underexplored. Using a qualitative case study approach, the research involved 20 participants, including counseling teachers, PIK-R administrators, and students. Data were collected through in-depth interviews, participant observation, and document analysis, enabling the capture of social dynamics and meaning-making processes. Findings reveal that religious character formation emerges through everyday interactions, negotiations of Islamic values, and students’ participation in PIK-R activities. Rather than functioning as a mechanical program, PIK-R provides a space where students internalize values and construct religious identity through dialogue between institutional guidance and personal experience. The study highlights the interpretive dimension of character development, showing how meaning is co-created in the counseling context. The implications suggest that PIK-R can serve as a unique arena for religious character education, enriching youth counseling practices with Islamic values. However, the study is limited to one school context, and further research across diverse settings is needed to deepen understanding of these dynamics.